Somnambulism - a rare cause of a serious accident. Case report - Karolina Rożenek; Tomasz Krzysztof Bąk; Jolanta Wojciechowicz; Anna Gawęda; Tomasz Tomaszewski (Kazimierz Wielki University, 2018)
Somnambulism is usually seen as a mild state,  associated with sleep disorders, excessive daytime sleepiness, tiredness, mental disorders and reduced quality of life. It is potentially a life-threatening condition. A 21-year-old man was admitted after a fall from the balcony from the height of the first floor.